Activation of peroxymonosulfate by cow manure biochar@1T-MoS2 for enhancing degradation of dimethyl phthalate: Performance and mechanism - He, Yutian; Wang, Xinzhi; Ke, Yuhan; Qiu, Yiquan; Zhou, Qiao; Shen, Zheyu; Xie, Han; Li, Yingqiang; Huang, Mingzhi (Frontiers in Environmental Science, 2023)
Dimethyl phthalate (DMP) which has been widely detected in water is neurotoxic to humans and should be effectively eliminated. Persulfate-based advanced oxidation processes are considered to be reliable methods aiming at emerging contaminants degradation, while an efficient catalyst is urgently needed for the activation of the reaction. As a typical 2D material, 1T-MoS2 is expected to be applied to the activation of persulfate owing to its abundant active sites and excellent electrical conductivity. In practical applications, 1T-MoS2 has the phenomenon of reunion which affects the exposure of its catalytic sites. Therefore, in this study, we used waste cow manure as a raw material to prepare biochar and achieved high exposure of 1T-MoS2 activation sites by loading 1T-MoS2 onto the surface of cow manure biochar through hydrothermal synthesis. The prepared composite catalytic material CMB@1T-MoS2 was used to activate PMS for the degradation of DMP. It was found that CMB@1T-MoS2 has better effect than CMB or 1T-MoS2 alone for the degradation of DMP, reaching 77.65% at pH =3. Under alkaline conditions, the degradation rate of DMP was reduced due to the inhibition of the catalytic process. Among the different coexisting anions, HCO-3 interfered and inhibited the degradation process the most, leading to the lowest degradation rate of DMP with 42.45%. The quenching experiments and EPR analysis showed that SO-4• and •OH were the main ROS in the CMB@1T-MoS2/PMS process. This study promotes the resourceful use of cow manure and is expected to provide a novel persulfate-based advanced oxidation process catalyzed by CMB@1T-MoS2 for the elimination of DMP in an aqueous environment.